Modelagem matemática do escoamento superficial sob o efeito da cobertura vegetal em um Latossolo argiloso - Chang, Pablo (2022)
The dragging of soil particles and nutrients by surface runoff can substantially compromise agricultural productivity. Statistical and mathematical modeling is a tool that can be used to estimate water, soil, and nutrient losses according to soil management. This thesis was divided into two chapters with different strategies to model surface runoff. In Chapter 1, a statistical modeling was carried out with data on water, soil and nutrient losses, collected in the field during the years 2017 to 2020 of soybean and corn crops in the experimental area of the Instituto de Desenvolvimento Rural do Paraná (IDR-Paraná), regional hub of Santa Tereza do Oeste. Regression models were constructed that relate variables of rainfall intensity, soil density, macroporosity, straw dry mass, terrain slope and soybean or corn cultivation. Chapter 2 focuses on semi-empirical modeling, with calculations in the kinematic equation of the wave, applied to data obtained through a rainfall simulator. In the adapted model, three levels of straw coverage were evaluated, comparing the use of Philip's and Kostiakov's models. The simulator, developed and built for this and future research in the area, has a manual hoist system to change the slope of the soil, in addition to being equipped to perform electronic readings of flow and soil moisture. The results of Chapter 1 showed that the adjustments for straw cover presented a good estimate, and the highest losses are related to the type of crop and straw cover and higher levels of compaction generate higher erosion losses. While the results of Chapter 2 showed that the built simulator showed high potential for the study of soil erosion. The use of the Kostiakov model in surface runoff showed a better fit to the data in relation to the Philip model.